Perancangan Game Pembelajaran Pengucapan Bahasa Inggris Berbasis Pengenalan Suara - Fikri Ihsan Ahmad; Tri Afirianto; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
English is the language of all countries in the world in its position as a global lingua franca. Indonesia must place English in a very important and urgent position as a global player, in order to be come more competitive in international market competition. English education in Indonesia has been conducted since elementary school, but the learning process only focuses on mastering vocabulary and grammar, without regard to mastering pronunciation. Educational games can be interactive learning media for mastering English pronunciation, making the learning process more fun and effective. International Poetic Alphabet (IPA) is a symbol that can represent the sounds of English pronunciation, for facilitate the learning process. Iterative Prototyping is a research method used to design and implement English pronunciation learning games, each will iterated to meet the needs of the target players. The design is an iteration process that produces a prototype paper, from the collection of needs analysis to the target user. The implementation is an iteration process that produces a digital prototype base on the design, that can be played on the Android mobile platform. The results of the study show that educational games can have a positive influence on English pronunciation skills.